Biodiversity and Geographic Distribution of Rhizobia Nodulating With Vigna minima - Liu, Guohua; Liu, Xiaoling; Liu, Wei; Gao, Kangning; Chen, Xiaoli; Wang, En-Tao; Zhao, Zhenjun; Du, Wenxiao; Li, Yan (Frontiers in Microbiology, 2021)
Vigna minima is a climbing annual plant widely distributed in barren wilderness, grass land and shrub bush of China and other country such as Japan. However, the rhizobia nodulating with this plant has never been systematically studied. In order to reveal the biodiversity of nodulating rhizobia symbiosis with V. minima, a total of 874 rhizobium isolates were obtained from root nodules of the plant spread in 11 sampling sites of Shandong Peninsula, China, and they were designated as 41 haplotypes in the genus Bradyrhizobium based upon recA sequence analyses. By multilocus sequence analysis (MLSA) of 5 housekeeping genes (dnaK, glnII, gyrB, recA and rpoB), the 41 strains representing different recA haplotypes were classified into 9 defined species and 9 novel genospecies. Bradyrhizobium elkanii, Bradyrhizobium ferriligni and Bradyrhizobium pachyrhizi were the predominant and universal distributed groups. The phylogeny of symbiotic genes of nodC and nifH showed similar topology and phylogenetic relationships, in which all the representative strains were classified into 2 clades grouped with strains nodulating with Vigna spp., demonstrating that Vigna spp. shared common nodulating groups in the natural environment. All the representative strains formed nodules with V. minima in nodulation test performed in green house conditions. The correlation between V. minima nodulating rhizobia and soil characteristics analyzed by CANOCO indicate that available nitrogen, total nitrogen and organic carbon in the soil samples were the main factors affecting the distribution of rhizobia isolated in this study. This study systematically uncovered the biodiversity and distribution characteristics of V. minima nodulating rhizobia for the first time, which provided novel information for the formation of the corresponding rhizobium community.